Cracking the green wall code: insights into cell wall integrity across organisms - Vukašinović, Nemanja; Serif, Manuel; Bacete, Laura (Frontiers in Plant Physiology, 2023)
Cell walls are not just passive barriers; they are dynamic and adaptable structures that are actively remodeled in response to both internal and external cues. They are crucial in defining cellular identity, ensuring structural integrity, and mediating interactions with the environment. The concept of cell wall integrity (CWI) encompasses the mechanisms by which cells monitor and maintain their walls, ensuring proper function and response to challenges. While significant knowledge has been accumulated on CWI in certain model organisms, there remains a vast landscape of uncharted territory in others. In this review, we aim to bridge this gap, offering a comparative perspective on CWI across different evolutionary lineages, from the well-studied yeasts to the diverse world of plants. We focus especially on the green lineage –the group of green algae and land plants, hence the green wall–, but also consider some insights from organisms with radically different lifestyles and cell wall arrangements, which serves as a base to some intriguing questions about the role of CWI across evolution and environmental adaptation.